Pharmaceutical quality of antibiotics in Small Island Nations in the Western Pacific region: a pilot survey. (11th September 2019) - Scrimgeour, Sophia; Nunan, Michael; Sanburg, Amanda L. C.; Jones, Alison; Narkowicz, Christian; Jacobson, Glenn A.; Schneider, Jennifer J.; McLachlan, Andrew J.; Quilty, Simon
Abstract: Background: Australia's closest neighbours in the Western Pacific face many procurement, distribution and regulatory challenges providing patients with quality pharmaceuticals on limited budgets. This study tested the hypothesis that some antibiotics being used within the healthcare systems of Papua New Guinea, Vanuatu and the Solomon Islands were substandard, and through this pilot project explored challenges and constraints around collaborative regional pharmaceutical quality testing opportunities. Methods: A list of 11 commonly used and 'essential' acute care intravenous and oral antibiotic products was compiled. A purposive sample of 20 units of each listed medicine was collected at the earliest possible point of the supply chain within the three participating nations. These samples were transported to Australia for analysis. Results: All oral and intravenous product samples complied with uniformity of mass standards, except for oral amoxicillin from Country 3. Most antibiotics showed uniformity of content except for cloxacillin. Conclusion: Most samples met quality standards, except for cloxacillin, which failed dramatically and this may indicate increased susceptibility to degradation in tropical settings. Although the results are reassuring compared with recent studies of pharmaceutical quality in this region, products of substandard quality were identified. The issues encountered in the timely testing of samples demonstrate the need for innovative solutions to promote pharmaceutical quality assurance, particularly in resource‐limited settings. Strategic regional cooperation could greatly increase testing capability for Small Island Nations, benefiting the most vulnerable populations and strengthening antibiotic stewardship across the region.